Acceptability, Attitude and Utilization Towards Telemedicine among People of Southern Punjab during COVID19 Pandemic - Muhammad Bilal Ghafoor, Gul Muhammad Shaikh, Faiza Sarwar, Ghulam Mustafa, Sana Khan, Shamraiza Zulfiqar (Pakistan Journal of Medical & Health Sciences, 2022)
COVID-19, highly infectious, respiratory illness caused by SARS-CoV2 (Severe Acute Respiratory Syndrome) virus. It has devastating effects with high mortality.Infection become worse in patients with pre-existing medical conditions. Hospitals increased the number of critical care units in order to stabilize the pandemic’s crisisand to minimize person to person transmission, installation of telemedicine networks, distant workers and internet-based health visits. Objective: To assess the acceptability, attitude and utilization towards telemedicine among COVID19 pandemic. Materials and Methods: In Sheikh Zayed Hospital, Rahim Yar Khan, a telemedicine network was quickly set during COVID-19 epidemic. A descriptive cross-sectional study comprising 144 study subjects aged between 34-58 year who seek telemedicine problems of surgery, cardiology, ENT, dermatology, gynaecology and obstetrics, pulmonology, medicine and paediatrics. Results: Out of 144 study subjectswith telemedicine consultation percent distribution of ENT and pulmonology was (48) 33.3% followed by medicine, gynaecology and obstetrics, dermatology, pediatrics and surgery.Patient’s satisfaction level was 62.5% in cardiac patients. In department of gynaecology and obstetrics patients satisfaction towards telemedicine was 88.9%, (65%) patients in medicine were satisfied, followed by surgery 41.7%. Gender wise distribution showed 64.1% males were satisfied followed by 61.3% females Conclusion: The COVID-19 pandemic is creating a historic global challenge for health care providers, patients, and societies. Telemedicine is now widely available at low-cost, and broadly acceptable by physicians and patients. Current study highlights the use of telemedicine and effective applications throughout COVID-19 crisis. Telemedicine played an important role for medical practitioners to manage the COVID-19 situation. Keywords: Telemedicine, COVID-19, Pandemics, Crisis, Gynaecology and Obstetrics